Current regulatory requirements for stability studies of biological medicinal products: a review - A. A. Soldatov; A. K. Yakovlev; Zh. I. Avdeeva; D. V. Gorenkov; A. S. Korovkin; V. V. Kosenko (Биопрепараты: Профилактика, диагностика, лечение, 2024)
INTRODUCTION. The stability assessment of biological medicinal products (BMPs) requires special approaches and regulatory requirements. Therefore, BMPs require relevant national guidelines, which are an important prerequisite for the assurance of the safe and effective use of BMPs.AIM. This study aimed to analyse national and international requirements for the stability assessment of BMPs in order to use the results to inform future development of a unified regulatory approach to estimating and confirming shelf-life periods for BMPs.DISCUSSION. Most biotechnological medicinal products (BTMPs) are proteins and are highly sensitive to environmental factors by nature. Therefore, the shelf life of a BTMP is established on the basis of real-time stability studies. Stability testing under accelerated and stress conditions is conducted to support shelf-life claims and to characterise the mechanism of protein structure degradation. The results of accelerated and stress studies can be used to select the most sensitive stability-indicating parameters and testing methods. National and international regulatory authorities have developed specialised guidelines for stability studies of BMPs of various origins, and the stability assessment approaches in the regulatory system of the Eurasian Economic Union (EAEU) are harmonised with international standards. Special considerations associated with the stability of vaccines imply that stability studies of vaccines should not only establish shelf life but also investigate stability after reconstitution and after short-term temperature excursions from the recommended cold-chain conditions.CONCLUSIONS. Special stability testing considerations for various groups of BMPs (including BTMPs and immunobiologicals) indicate the need to develop and improve the system of requirements for BMP stability assessment. This will facilitate the optimisation of the life cycle of BMPs in the Russian Federation and the other EAEU member states.